Perancangan Sistem Informasi Pembayaran dan Pengelolaan Keuangan di ARC Group - Harahap, Muhammad Jamil Ikhsan; Saputra, Andre; Diansyah, Risnal (LPPM STT Terpadu Nurul Fikri, 2024)
An information system integrates data transformed and managed into good, clear and useful information for its users. Designing a system requires processes and data that will be determined by the design. Unified Modeling Language (UML) is a standard language widely used in the industrial world in graphical modelling, which aims to analyze, visualize and explain how a system works. This research focuses on designing payment and managing finance information systems at ARC Group (PT. An cipta Wisata Riau branch). The main objective is to simplify the ordering, payment, and financial management process, which is done manually. The design of this system will make it easier for customers to order tour services and make payments. It will make it easier for administrators to manage finances at ARC Group (PT. An cipta Wisata Riau branch). This research uses a linear sequential method (waterfall) for system development, using HTML, CSS, PHP, JavaScript, and Visual Studio Code text editor for database management and includes rigorous testing to ensure quality. The expected result is an effective and easy-to-use system to support the operational activities of ARC Group (PT. An cipta Wisata Riau branch).